On the Hyperspace of Convex Compact Subsets of the Tikhonov Cube - Ivanov, A. S.; Zarichnyi, M. M. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We prove that the hyperspace of compact convex subsets of the Tikhonov cube \(I^ω_1\) is homeomorphic to \(I^ω_1\) .